Sustainability evaluation of sheep production in the páramo ecosystem of Cerrito Santander municipality, Colombia - Jaimes, Gustavo; Flórez, Dixon; Villamizar, César (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
The preservation of natural resources and the production of enough food to meet the demands of a growing human population, will be one of the most important challenges that the world will have to face in the coming years, hence the need to promote the sustainable use of the resources. The objective of this research was to evaluate the sustainability of the sheep production system in the páramo ecosystem, municipality of Cerrito-Santander, Colombia. A survey was applied to 15 sheep farmers, allowing the characterization of the production system and the georeferencing of farms. This information was analyzed by applying descriptive statistics, using SPSS software, version 24, this allowed to present the most relevant aspects of sheep production in the sector. Participatory workshops were held with the producers, to select and evaluate the sustainability indicators of sheep production systems in the páramo area, which were visualized by a biogram or spider web graph. Finally, strategic guidelines were formulated to respond to the critical points of sheep production. Most producers prefer the commercialization of wool and the use of the animal's discarded stages to obtain economic income from the sale of meat. Critical points (food supplements, type of state support received, use of veterinary services and use of energy sources) and favorable points (cost of raw materials, food security and water sources) were evidenced for the economic, social and environmental dimensions. It is necessary to focus attention on the critical points and apply the strategic guidelines, since together with the favorable points they will allow generation and establishment of more sustainable sheep production systems.